Decrease in beneficial bacteria and increase in harmful bacteria in Gastrodia seedlings and their surrounding soil are mainly responsible for degradation of Gastrodia asexual propagation - Wang, Xi; Gao, Yugang; Zang, Pu; Zhang, Ge; Yang, Xinyu; Liu, Qun (Frontiers in Plant Science, 2024)
Introduction Asexual reproduction of Gastrodia elata Bl. f. glauca S. chow (GeB) produces degeneration with increasing number of GeB. Therefore, we analyzed the microorganisms of GeB seedlings and surrounding soil by Illumina Miseq high-throughput sequencing technology. Methods In this study, Illumina Miseq high-throughput sequencing technology was applied to analyze the types and quantities of GeB seedlings and surrounding soil microorganisms in the first to third generations of asexual reproduction, isolated and identified the dominant strains of GeB in the first to third generations and screened the antagonistic bacteria of its pathogenic fungi, and evaluated the effects of beneficial bacteria on the production performance of seedlings planted with GeB. Results With an increase in the number of asexual reproductive generations, the number of pathogenic fungi and bacteria in GeB seedlings and the surrounding soil increased, and the number of beneficial fungi and bacteria decreased. Pseudomonas sp., Agrobacterium rhizomes, and Herbaspirillum hiltneri were isolated and identified in the first generation, and Trichoderma harzianum, Penicillium viridiatum, Fusarium oxysporum, and Novosphingobium sp. Were isolated and identified in the third generation. Antagonistic strains of the three pathogenic bacterial strains were screened. In conclusion, beneficial bacteria significantly improved the production performance of asexual reproductive seedlings planted with GeB. Discussion In conclusion, our findings suggested that the microorganisms of GeB seedlings and the surrounding soil change as the number of generations of GeB reproduction increases, disrupts the microecological balance of surrounding soil and endophytic microbiomes.This study provides a theoretical basis for the degradation of asexual reproduction in GeB.